Ability of soil microorganisms to degrade aminopyralid and its effect on their growth - Martin Koudela; Miroslava Soukupová; Eva Jablonská; Tereza Šmrhová; Tomas Engl; Jaroslav Matějka; Sebnem Kurhan; Petr Maršík; David Novotný; Čeněk Novotný (Plant, Soil and Environment)
The study aimed at the isolation of microorganisms from aminopyralid (AP)-contaminated soil, evaluation of their ability to degrade AP, and examination of the effects of AP on microbial growth. Geotrichum candidum, Cladosporium herbarum, Candida subhashii, and Paenarthrobacter nicotinovorans were isolated and identified using enrichment. None of those strains were able to degrade 100 ppm AP within 2-3 weeks. In contrast, collection strains Pleurotus ostreatus 'Spoppo' and Bacillus velezensis FZB42 reduced AP concentration by 35.1% and 47.8%, respectively. Low sensitivity of growth to AP (400 ppm) on the malt-extract-agar medium was observed; inhibition values for C. herbarum and G. candidum were 52.4% and 22.8%, respectively, compared to 33.7% inhibition found with P. ostreatus 'Spoppo'. Promotion of fungal growth was observed at low AP concentrations in the Czapek-Dox medium, the highest effect being in G. candidum. The growth promotion effect was confirmed with P. ostreatus 'Spoppo'growing on wheat straw contaminated with Mustang Forte and Corello herbicides; total fruiting body mass yield increased 1.25- and 1.37-fold, respectively. The study offers insight into future strategies for mitigating the environmental impact of synthetic auxin herbicides.